2020
DOI: 10.1097/meg.0000000000001815
|View full text |Cite
|
Sign up to set email alerts
|

microRNA in inflammatory bowel disease at a glance

Abstract: Inflammatory bowel disease (IBD) as a chronic inflammation in colon and small intestine has two subtypes: ulcerative colitis (UC) and Crohn’s disease (CD). Genome studies have shown that UC and CD are related to microRNAs (miRNAs) expression in addition to environmental factors. This article reviews important researches that have recently been done on miRNAs roles in CD and UC disease. First, miRNA is introduced and its biogenesis and function are discussed. Afterward, roles of miRNAs in inflammatory processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 131 publications
0
15
0
Order By: Relevance
“…Studies of circulating miRNAs have shown that miRNAs are potential candidates as biomarkers for diagnosing IBD and various other diseases [ 57 , 58 , 59 , 60 , 61 ]. The high stability of miRNAs in the body fluids and the ability to obtain rapid and accurate quantitative estimates are some merits of using circulating miRNAs as biomarkers in IBD [ 28 ]. MiRNAs are not only interesting tools for diagnosis, but also for potential future therapeutic applications by miRNA mimics or miRNA antagonists [ 62 , 63 ].…”
Section: Mirnas In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of circulating miRNAs have shown that miRNAs are potential candidates as biomarkers for diagnosing IBD and various other diseases [ 57 , 58 , 59 , 60 , 61 ]. The high stability of miRNAs in the body fluids and the ability to obtain rapid and accurate quantitative estimates are some merits of using circulating miRNAs as biomarkers in IBD [ 28 ]. MiRNAs are not only interesting tools for diagnosis, but also for potential future therapeutic applications by miRNA mimics or miRNA antagonists [ 62 , 63 ].…”
Section: Mirnas In Ibdmentioning
confidence: 99%
“…MiRNA expression has been shown to be of importance in a wide variety of human diseases such as cancer, autoimmune, cardiovascular, and neurodegenerative diseases [ 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The miRNAs not only circulate in the human peripheral blood in a stable form, they are also present in other body fluids such as urine, saliva, milk, cerebrospinal fluid, and feces [ 25 , 26 , 27 , 28 ]. The miRNAs are engaged in disease origin and development, and some are pathology-specific [ 29 ], thus, changes in miRNA expression profiles have been addressed for applications in early detection as well as prognostics, diagnostic classification and drug response prediction.…”
Section: Microrna—an Introductionmentioning
confidence: 99%
“…MiRNAs are 21 to 25 nt in length [38][39][40] and regulates gene expression primarily by acting as post-transcriptional repressors [35,37]. miRNAs were first described in 1993 by Ambros and colleagues in Caenorhabditis elegans (C. elegans) as RNA molecules of 18 to 23 nt in length that regulate developmental timing [41][42][43][44][45][46]. Recently, several miRNA-size small RNA fragments with 15-26 nt in length have been identified in prokaryotes, such as Streptococcus mutans, Escherichia coli (E. coli), and Mycobacterium marinum.…”
Section: Mirna-size Moleculesmentioning
confidence: 99%
“…Though recognized most for its effects on the gastrointestinal tract, IBD is well known for harboring a multitude of complications, including extraintestinal. This largely stems from the chronic and systemic inflammatory state IBD induces via pathways such as NF-κB, STAT3, the NOD2 receptor family, and toll-like receptors (TLRs), which alter regulatory mediators such as cytokines and various miRNAs [ 5 , 7 ]. Perhaps the most well-studied is the strong association between IBD-induced colitis and increased colon cancer risk, arguably the most lethal complication of IBD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%